PENERAPAN MODEL PEMBELAJARAN TERPADU UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS III SD NEGERI 010 PERANAP KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Yulinar, Yulinar; Witri, Gustimal; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to increase the result of indonesian languange subject in the third class of SDN 010 Peranap Kecamatan Peranap Kabupaten Indragiri Hulu. Is applied best learning can increase the result of indonesian Language subject on the third class elementary school ? This research design is classroom research. Classroom research is practice research to repaired studying and learning on class. The research time and place are held on the thrid class SDN 010 Peranap Kecamatan Peranap Kabupaten Indargiri Hulu. Among of the student are 30 student 16 boys and 16 girls. And them the result as long as studying and learning process and result of studying indonesian language subject will be analyzed. On basic score that taken from range result of daily test student before applied best learning is 66,33. At first siclus on daily test I the range result of the student is 76,26, meeting will continue on the second siclus and can see the range of result studying indonesian subject on the result daily test II there is increasing by the result of student is 86,23. Result of studying have been complete is every student have been reach KKM by scoring 70 if means the student have successed to understanding . The increasing result of studying indonesian subject from basic score before applied best learning to siclus I and II after applied best learning method. Based on observation result the result of student learning that doing studying and learning process where is on activity, the student have been active after using best learning method. On siclus I the range percent activity learning student is 76,26% and on siclus II the range percent activity learning student is 86,23%. With the result that increasing activity student from acoring student from basic score to siclus I is 33% and next level from siclus I to siclus II is 38%.Keywords : Applied Best Learning Method